2000
DOI: 10.1016/s0370-2693(00)00235-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of glueball and production in the central region of pp collisions

Abstract: We explain the φ and t dependences of mesons with J P C = 0 ±+ , 1 ++ , 2 ±+ produced in the central region of pp collisions. For the 0 ++ and 2 ++ sector this reveals a systematic behaviour in the data that appears to distinguish between qq and non-qq or glueball candidates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The dk T (or ) dependence of central production has been studied intensively in nearly all WA102 publications; its implications are discussed in a series of papers by Close and collaborators [739,[742][743][744][745][746][747]. The study revealed two surprises.…”
Section: Central Productionmentioning
confidence: 99%
“…The dk T (or ) dependence of central production has been studied intensively in nearly all WA102 publications; its implications are discussed in a series of papers by Close and collaborators [739,[742][743][744][745][746][747]. The study revealed two surprises.…”
Section: Central Productionmentioning
confidence: 99%
“…They also provide copious data on γγ → light hadrons. Exploiting the dk T filter and φ dependences may separate qq states from those with gluonic admixtures or S-wave substructure (see later) [4]. Then there is the new opportunity for central production in proton-proton collisions at STAR and the proposal for this at HERA-g [3].…”
Section: Light Hadron Spectroscopy and Dynamics: Present And Futurementioning
confidence: 99%
“…Then, one could study, for instance, the distributions in the angle φ 12 between the transverse momenta p t,1 and p t,2 of the leading protons. For low-energy central-meson production these angular distributions have been extensively discussed in [7][8][9][10][11][12][13], [63][64][65], and from the tensor pomeron point of view in [33]. Angular distributions for glueball production have been discussed in [32].…”
Section: First Resultsmentioning
confidence: 99%